The Efficacy of the Direct Method for Young Learners: Integrating Phonetic Approaches and Visual Realia to Enhance Early Vocabulary and Speaking Skills - Thammineni, Haribabu (International Journal of Psychosocial Rehabilitation, 2020)
The Direct Method (DM) was the focus of this study, which examined its effectiveness in early language acquisition by young learners when the phonetic approach and visual realia were integrated to boost vocabulary mastery and speaking abilities. The critical period hypothesis, which suggests that early childhood is a neurologically “sweet” time for natural language learning, provides the basis for the research, which looks at the effects of an immersion, translation-free environment on beginner learners. The main method examined is that of the exclusive use of the target language, which establishes a direct mental connection between the concepts and the linguistic forms, without going through the “translation loop” that makes it difficult to become fluent. Results of various educational environments, such as bilingual schools in Andhra Pradesh and public elementary schools in India, suggest that the Direct Method is effective for enhancing oral competence. Systematic use of phonetic awareness, whereby they are taught the alphabet rhythms and vowel sounds, allows students to learn the correct pronunciation without reading. Moreover, the presence of visual realia, which are concrete materials, flash cards and multi-sensory materials, enables the learner to “catch” meaning in the context of the situation; hence, better retention of new words. Bearing in mind these achievements, the study also identifies the following conditions for the success of the method: the teacher's high level of professionalism, creativity and the small class size. The research results show that the Direct Method consumes a lot of instructional energy, but it has the advantage of stimulating students' motivation and confidence in language communication, which is more advantageous as a “good start” in the beginning of language learning. The following recommendations are made: Use a blended model to help span the gap between oral fluency and academic literacy when moving to higher educational levels.